Level of Knowledge and Use of Traditional Medicine in Outpatients of Mekarsari Health Center, Barito Kuala Regency - Rakhmatullah, Aditya Noviadi; Yunarti, Azmi; Chandra, M. Andi; Muliyati, Imas (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2024)
The use of herbal medicine as a treatment is increasing, especially in Mekarsari District, Barito Kuala Regency. Without proper education, traditional medicine practices can have a negative impact on health. The purpose of this study was to determine the level of knowledge and use of traditional medicine in patients seeking treatment at the Mekarsari Health Centre. This study used a descriptive method with a quantitative approach. The population in this study were all outpatients at the Mekarsari Health Centre in January 2023. This study used a purposive sampling technique in sampling and used a validated questionnaire instrument in data collection. The results showed that 47% of respondents had a sufficient level of knowledge, 25% had a good level of knowledge, 14% had a poor level of knowledge, and 13% had a poor level of knowledge. Based on the method of obtaining traditional medicine, it is known that 55% said that it was from herbal medicine sellers in the form of powder or infusions with a duration of use ranging from one to three days. The majority of traditional medicine users use it to relieve pain and aches (22%). Based on the effects after consuming traditional medicine, 78% said they felt better and 99% said they had no side effects.